2022
DOI: 10.29133/yyutbd.1136189
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Identification of Volatile Compounds in Rosa laxa Retz var harputense T. Baytop "Kişmiri rose"

Abstract: The gardening of ornamental plants comes back to ancient times (Urartians). Nowadays the gardening of ornamental plants is done worldwide as in the Van provinces of Türkiye. Old and traditional gardens can be seen in different regions of this province naturally. Among these plants, Rosa laxa Retzius var. harputense T. Baytop (Kişmiri rose), is an exotic plant coming from Central Asia. Kişmiri rose has semi-double and miniature flowers and blooms for about five months in the ecological conditions of Van. It has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Hexane takes up non-polar compounds found in plants well because of its polarity (Ghazali and Yasin, 2016). Identify secondary metabolites using compound separation tools such as Gas Chromatograph -Mass Spectrophotometer (GC-MS) (Alp et al 2022). In research by Neda et al (2013), water and methanol extracts of butterfly pea flowers were identified as having the main compound, inositol, which is effectively used as an anticancer against several types of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Hexane takes up non-polar compounds found in plants well because of its polarity (Ghazali and Yasin, 2016). Identify secondary metabolites using compound separation tools such as Gas Chromatograph -Mass Spectrophotometer (GC-MS) (Alp et al 2022). In research by Neda et al (2013), water and methanol extracts of butterfly pea flowers were identified as having the main compound, inositol, which is effectively used as an anticancer against several types of cancer.…”
Section: Introductionmentioning
confidence: 99%